2015
DOI: 10.1063/1.4936877
|View full text |Cite
|
Sign up to set email alerts
|

Experiments of air bubbles impacting a rigid wall in tap water

Abstract: Trajectory and impact dynamics of bubbles in tap water were studied. Results confirm that bubbles with identical radii can be classified in two categories: fast bubbles and slow bubbles. Each category of bubble can describe zig-zag or helical motion. The aspect ratio and terminal velocity of a bubble depend on its radius and category. Restitution relations are also presented for the two categories of bubble after impact with an horizontal wall. With these relations, the state of a bubble after rebound can be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Tsao and Koch [13] found that the collision mechanism can be explained by the transition among the kinetic energy, surface energy, and potential energy. Pelletier and Béguin [14] experimentally investigated that, based on the restitution relations, the aspect ratio of a bouncing bubble before a rebound can be predicted after a rebound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsao and Koch [13] found that the collision mechanism can be explained by the transition among the kinetic energy, surface energy, and potential energy. Pelletier and Béguin [14] experimentally investigated that, based on the restitution relations, the aspect ratio of a bouncing bubble before a rebound can be predicted after a rebound.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, previous research has been devoted to studying the dynamics of bubbles collision with surfaces [14], the directional and continuous transport of bubbles on superhydrophobic plates [19], or isotropic spreading on SALSs [15]; however, to our knowledge, no results aimed at the anisotropic spreading of bubbles on the SALSs have yet been reported. The anisotropic spreading of bubbles on the designated superaerophilic areas may motivate the novel technologies to enhance or reduce the reaction rate, mass, and heat transfer rate in some specific positions and then to improve the equipment performances in mineral flotation, selective aeration, bubble reactors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Due to our focus on small bubbles of a radius less than 1 mm, we only consider either spherical or slightly ellipsoidal shaped bubbles. In terms of the interfacial mobility, the bubble dynamics can be classified into two cases of mobile (or fast bubble) and immobile bubbles (or slow bubbles) [35,51]. If a bubble-liquid interface is contaminated by particulates or surfactants, the interface holds a condition of zero tangential velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a condition of zero tangential shear stress is applied and as a consequence, a mobile bubble achieves a higher terminal velocity [35]. From a practical point of view, bubbles in tap water are observed to be both mobile and immobile bubbles [51,53]. As a bubble approaches the wall, a thin liquid-film forms between the bubble and the substrate and the surface wettability does not change the bubble dynamics as long as a thin film exists [76].…”
Section: Introductionmentioning
confidence: 99%